2009
DOI: 10.1016/j.ijid.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated extrapulmonary tuberculosis in Thailand: epidemiology and risk factors for death

Abstract: Among HIV-infected patients with TB, extrapulmonary disease occurred in 40% of the patients, particularly in those with advanced immune suppression. Death during TB treatment was common, but the risk of death was reduced in patients who took co-trimoxazole, fluconazole, and antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 21 publications
5
54
2
8
Order By: Relevance
“…There was 1 (2%) mortality noted in our series and that too after the patient was discharged from hospital as compared to 59 (19%) in Nara Kingkaew, et al 34 case series.…”
Section: Observation and Resultscontrasting
confidence: 46%
“…There was 1 (2%) mortality noted in our series and that too after the patient was discharged from hospital as compared to 59 (19%) in Nara Kingkaew, et al 34 case series.…”
Section: Observation and Resultscontrasting
confidence: 46%
“…Although pulmonary tuberculosis is the predominant form of infection, extrapulmonary tuberculosis constitutes up to 20% of reported cases, approximately 1 to 5% of which are attributed to tuberculosis of the central nervous system (CNS-TB) (2). CNS-TB occurs primarily in childhood but significantly increases in adults under conditions of immune suppression, which are associated with considerable morbidity and mortality (3,4). Pathogenesis of CNS-TB is initiated as a secondary infection during hematogenous dissemination of pulmonary infection to the brain parenchyma (5).…”
mentioning
confidence: 99%
“…Consequently, HIV status should be defined if TBM is recognized [9]. Furthermore, sever immunosuppression, increases the odds of having TBM [36,37]. Leeds and al were reported that HIV infected patients with extrapulmonary TB and CD4 less than 100 were more likely to have TBM [4].…”
Section: Issn: 2373-8995mentioning
confidence: 99%